OLYMPIC PEACE CONSOLIDATION (Fiep Bulletin - online, 2012)
Since the first Olympic event, in 1896, the Modern Olympic Games have had political problems - attempts to weaken the event, cancellations because of conflicts involving countries historically important in the context of sport, and other reasons in conflict with the rules of the International Olympic Committee, which recognize the concepts of Education, Fraternity and Peace.This series of unhappy events, which prejudiced the legitimate organization of the Olympiads, continued until 1988 in Seoul, but were not repeated in Barcelona (1992), Atlanta (1996) and Sidney (2000), which leads us to believe that, finally, Olympic Peace is now an affirmative process.